Rebanhos leiteiros com mastite causada por Staphylococcus aureus: diagnóstico e controle - Breno de Oliveira Silva (2006)
Petrifilm Staph Express and the Lavac Staph vaccine, were evaluated to support S. aureus infections diagnosis and control in dairy herds. For detection of S. aureus in milk samples, Petrifilm was highly sensitive but varied in specificity according to interpretive criteria and trainning level of the person who reads the plates. Results were easier and faster achieved, if compared to standard culture techniques, showing potential for on-farm use in S. aureus treatment or control programs. The Lavac Staph vaccine was evaluated in cows with S. aureus infections during lactation or at dry-off. Vaccination increased S. aureus infections cure rates when associated to the dry cow therapy, showing efficacy on pathogen control of a high prevalence herd. During lactation, vaccination had no impact on S. aureus cure rates and its use was not justified. The S. aureus incidence was not decreased in any of the studied phases.